ANALISIS TINGKAT RISIKO GERAKAN TANAH DI KECAMATAN PEKUNCEN KABUPATEN BANYUMAS - Risdianto, Risdianto (Jurnal Geografi, 2013)
Banyumas highly vulnerable to landslides. These conditions require researchonlandslide risk levels. Geographical information about the landslides risk is veryimportant to reduce the disaster vulnerability level. Spatial presentation ofdisaster will be very useful to society because it can be used to identify disasterproneareas. Pekuncen subdistricts in Banyumas have relief with a heightbetween 500 meters to 1200 meters above sea level. Slope is dominated bymedium to steep (8% - 25%). The highest rainfall average is 221 mm, with anannual rainfall of 2,648 mm height and number of rainy days 266 days. Based onthese data it appears that the region is prone to landslides. The method used isdescriptive quantitative analysis with spatial analysis using ArcGIS to analyzephysical and social parameters so that the result of the landslides level of dangerand landslide risk level can be used as reference in disaster mitigation efforts inthe district of Pekuncen, Banyumas Regency.